Neuroimaging in moderate MDMA use: A systematic review. (March 2016) - Mueller, F.; Lenz, C.; Steiner, M.; Dolder, P.C.; Walter, M.; Lang, U.E.; Liechti, M.E.; Borgwardt, S.
Highlights: Systematic neuroimaging review of moderate MDMA use in humans. No effect of moderate MDMA use on brain structure and function. High methodological heterogeneity and small sample sizes. Abstract: MDMA ("ecstasy") is widely used as a recreational drug, although there has been some debate about its neurotoxic effects in humans. However, most studies have investigated subjects with heavy use patterns, and the effects of transient MDMA use are unclear. In this review, we therefore focus on subjects with moderate use patterns, in order to assess the evidence for harmful effects. We searched for studies applying neuroimaging techniques in man. Studies were included if they provided at least one group with an average of <50 lifetime episodes of ecstasy use or an average lifetime consumption of <100 ecstasy tablets. All studies published before July 2015 were included. Of the 250 studies identified in the database search, 19 were included. There is no convincing evidence that moderate MDMA use is associated with structural or functional brain alterations in neuroimaging measures. The lack of significant results was associated with high methodological heterogeneity in terms of dosages and co-consumption of other drugs, low quality of studies and small sample sizes.